2021
DOI: 10.1002/er.7173
|View full text |Cite
|
Sign up to set email alerts
|

Structural control of crumpled sulfur‐assisted reduced graphene oxide with elemental sulfur for supercapacitor

Abstract: Summary Crumpled graphene oxide (C‐GO), a three‐dimensional (3D) structured material, has many advantages that can be of value in high‐performance supercapacitor electrodes. However, graphene oxide loses its morphology and advantages during the solution reduction process with polar solvents, which leads to restacking of individual sheets. In this work, we introduce an eco‐friendly and simple C‐GO reduction method using elemental sulfur. Since sulfur is a nonpolar and antisolvent for the hydrophilic C‐GO, sulfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
(96 reference statements)
0
1
0
Order By: Relevance
“…[36] The today's performance of most GO/polymer hybrid materials employed as electrodes in SCs, as quantified by its specific capacitance, amounts typically in the range of 100-300 F g À1 . [37][38][39] Importantly, the crucial obstacle hampering the practical application of GO-based hybrids in SCs is the low energy density, being usually two orders of magnitudes lower than in case of Li-ion batteries and typically reaching values up to 5-15 Wh kg À1 in case of aqueous electrolytes. [40] Notably, Song and co-workers showed that the use of 1-butyl-3-methyl-imidazolium tetrafluoroborate electrolyte allows a high energy density of 51 Wh kg À1 to be obtained, demostrating the high potential of organic electrolytes for widening of the potential window.…”
Section: Introductionmentioning
confidence: 99%
“…[36] The today's performance of most GO/polymer hybrid materials employed as electrodes in SCs, as quantified by its specific capacitance, amounts typically in the range of 100-300 F g À1 . [37][38][39] Importantly, the crucial obstacle hampering the practical application of GO-based hybrids in SCs is the low energy density, being usually two orders of magnitudes lower than in case of Li-ion batteries and typically reaching values up to 5-15 Wh kg À1 in case of aqueous electrolytes. [40] Notably, Song and co-workers showed that the use of 1-butyl-3-methyl-imidazolium tetrafluoroborate electrolyte allows a high energy density of 51 Wh kg À1 to be obtained, demostrating the high potential of organic electrolytes for widening of the potential window.…”
Section: Introductionmentioning
confidence: 99%